Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Assessing the fidelity of clay-size lithium isotopes as chemical-weathering tracers in detrital sedimentary successions - Xia Zhang; Chunming Lin; Robert W. Dalrymple; Cheng Cao; Daidu Fan; Guyue Tan; Xin Li (Geochimica et Cosmochimica Acta, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Decoding wildland-urban interface fire regimes in Hong Kong - Yizhou Li; Zhiqing Pan; Cong Gao; Chunming Shi; Shaorun Lin; Xinyan Huang (Urban Forestry & Urban Greening, 2025)

Enhancing cyclodextrin glycosyltransferase-mediated potato starch modification via plasma-activated water and twin-screw extrusion treatment - Fanglei Zou; Hongyun Hao; Miao Yang; Chunming Tan; Lin Chen; Junhua Wu; Hongying Wang (Food Chemistry, 2025)

Response of phosphorus burial and post-depositional diagenesis to postglacial climate change in the coastal system - Shuya Huang; Xia Zhang; Yanyan Zhao; Chunming Lin (Marine Geology, 2025)

Modifying buried heterogeneous contacts to promote efficient carrier extraction for efficient perovskite solar cells - Lei Gu; Jiacheng Su; Ruiqian Chen; Haoran Deng; Lei Zhao; Chunming Yang; Lin Song (Chemical Engineering Journal, 2025)

Sea-level and climatic evolution in the postglacial Qiantang River incised-valley system: Insights from grain-size end-member modeling and geochemical characteristics - Xia Zhang; Xueqian Zhou; Guyue Tan; Shuya Huang; Xin Shan; Chunming Lin; Xiaotian Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

Capacitive deionization exploiting La-based LDH composite electrode toward energy efficient and selective removal of phosphate - Chunming Feng; Xiaobing Pan; Xiaocheng Lin; Yi Yang; Fuqiang Fan; Chenxiao Jiang; Ying Mei (Desalination, 2025)

Baicalin attenuates acute skin damage induced by ultraviolet B via inhibiting pyroptosis - Zuohao Liu; Bingrong Dang; Zhen Li; Xingsheng Wang; Yuhan Liu; Fen Wu; Xinhui Cao; Chunming Wang; Changjun Lin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Age dating of Paleocene Meirenfeng Formation and its significance for the hydrocarbon source rocks in the East China Sea basin - Huaizhi Xu; Weifeng Shen; Dewen Qin; Yun Liu; Bocheng Zhang; Chunming Lin; Xiyun Wang (Marine and Petroleum Geology, 2024)

Late Neolithic to Bronze Age water management and upland rice cultivation in the mountainous areas of Southeastern China Coast - Guiping Wu; Xinxin Zuo; Wei Wu; Lin Ren; Chunming Wu; Yingjun Lin; Hui Xie; Yaoyao Pei; Guiyu Zhou (Quaternary International, 2024)

Effects of iron additives on the removal of antibiotics and antibiotic resistance genes in anaerobic fermentation of food waste - Xiaotian Li; Langping Zhu; Rong Ma; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

Effects of zero-valent iron and magnetite on ethanol and lactic acid production in the anaerobic fermentation of food waste - Xiaotian Li; Rong Ma; Langping Zhu; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

Heavy metals transport patterns and risk evaluation in the pig manure- black soldier fly-tilapia food chain - Changquan Lin; Xiting Xia; Yuwei Li; Rong Ma; Langping Zhu; Xiaotian Li; Youqian Tang; Chunming Wang (Environmental Pollution, 2023)

Storm-driven variations in depositional environments modify pyrite sulfur isotope records - Kaixi Jiang; Chunming Lin; Xia Zhang; Yanyan Zhao; Xianguo Lang; Ming Su; Ce Wang; Yaping Lei; Jiarui Liu (Earth and Planetary Science Letters, 2023)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

OPEN GLUME1: a key enzyme reducing the precursor of JA, participates in carbohydrate transport of lodicules during anthesis in rice - Xiaohui Li; Yihua Wang; Erchao Duan; Qi Qi; Kunneng Zhou; Qiuyun Lin; Di Wang; Yunlong Wang; Wuhua Long; Zhigang Zhao; Zhijun Cheng; Cailin Lei; et al. (Plant Cell Reports, 2018)

Segmental allotetraploidy generates extensive homoeologous expression rewiring and phenotypic diversity at the population level in rice - Yue Sun; Ying Wu; Chunwu Yang; Shuai Sun; Xiuyun Lin; Lixia Liu; Chunming Xu; Jonathan F. Wendel; Lei Gong; Bao Liu (Molecular Ecology, 2017)
Allopolyploidization, that is, concomitant merging and doubling of two or more divergent genomes in a common nucleus/cytoplasm, is known to instantly alter genomewide transcriptome dynamics, a phenomenon referred to as “transcriptomic shock.” However, the immediate effects of transcriptomic alteration in generating phenotypic diversity at the population level remain underinvestigated. Here, we employed the MassARRAY‐based Sequenom platform to assess and compare orthologous, allelic and homoeologous gene expression status in two tissues (leaf and root) of a set of randomly chosen individuals from populations of parental rice subspecies ( indica and japonica ), in vitro “hybrids” (parental mixes), reciprocal F1 hybrids and reciprocal tetraploids at the 5th‐selfed generation (S5). We show that hybridization and whole genome duplication ( WGD ) have opposing effects on allelic and homoeologous expression in the F1 hybrids and tetraploids, respectively. Whereas hybridization exerts strong attenuating effects on allelic expression differences in diploid hybrids, WGD augments the intrinsic parental differences and generates extensive and variable homoeolog content which triggers diversification in expression patterning among the tetraploid plants. Coupled with the vast phenotypic diversity observed among the tetraploid individuals, our results provide experimental evidence in support of the notion that allopolyploidy catalyses rapid phenotypic diversification in higher plants. Our data further suggest that largely stochastic homoeolog content reshuffling rather than alteration in total expression level may be an important feature of evolution in young segmental allopolyploids, which underlies rapid expression diversity at the population level.

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

The catalytic subunit of magnesium-protoporphyrin IX monomethyl ester cyclase forms a chloroplast complex to regulate chlorophyll biosynthesis in rice - Weiyi Kong; Xiaowen Yu; Haiyuan Chen; Linglong Liu; Yanjia Xiao; Yunlong Wang; Chaolong Wang; Yun Lin; Yang Yu; Chunming Wang; Ling Jiang; Huqu Zhai; et al. (Plant Molecular Biology, 2016)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)

Dramatic genotypic difference in, and effect of genetic crossing on, tissue culture-induced mobility of retrotransposon Tos17 in rice - Chunjing Lin; Xiuyun Lin; Lanjuan Hu; Jingjing Yang; Tianqi Zhou; Likun Long; Chunming Xu; Shaochen Xing; Bao Qi; Yingshan Dong; Bao Liu (Plant Cell Reports, 2012)

Study of phenol biodegradation using Bacillus amyloliquefaciens strain WJDB-1 immobilized in alginate–chitosan–alginate (ACA) microcapsules by electrochemical method - Daban Lu; Yan Zhang; Shiquan Niu; Letao Wang; Shaoxiong Lin; Chunming Wang; Weichun Ye; Chunlei Yan (Biodegradation, 2012)